"This place means freedom to me": needs-based engagement with marginalized migrant Muslim women in London. (22nd August 2020) - Thompson, Naomi; Nasimi, Rabia
Abstract: This paper draws on a case study of a community-based organization working with marginalized Muslim women in London from refugee and migrant backgrounds. The organization delivers a model of practice that involves English for Speakers of Other Languages (ESOL) classes, practical/informative workshops, and social integration in a women-only community space rather than these elements being accessed separately in often formal spaces. The article draws on data collected as part of the first year of an evaluation of a three-year funded project to engage the women. The data include registration information about the participant group, a bespoke workshop evaluation form completed by the women each month, and interviews with beneficiaries, volunteers, and staff. Our research finds that an integrated, bottom-up approach is successful in engaging isolated women and impacts on their lives through increased well-being, knowledge and skills, empowerment, and freedom. Whilst asset-focused interventions have become dominant in community development, there is a danger that a deliberate focus away from the needs of vulnerable groups may cement rather than tackle inequalities, and collude with a political and neoliberal agenda that promotes individualism and austerity. We argue it is necessary to develop interventions that respond to the needs of marginalized groups before building on people's strengths to address them. Our case study offers evidence for this.